Corporate Purpose Through a Māori Lens - Piripi, Mihiarangi; Peat, Briar (Victoria University of Wellington Law Review, 2025)
Corporate purpose for Māori organisations involves broader considerations than the maximisation of profit. This is consistent with tikanga and the context in which Māori organisations operate. In this article, we set out the background to the recent amendment to s 131 of the Companies Act 1993 which explicitly permits directors to consider matters other than the maximisation of profit when considering the best interests of a company. We also consider corporate purpose through a Māori lens, before commenting on the reference to the principles of the Treaty of Waitangi | te Tiriti o Waitangi in the original Bill. Lastly, we discuss of the use of tikanga as a better framework, and how that may work in practice.